2009
DOI: 10.1016/j.resp.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent adaptation in the hemodynamic response to hypoxia

Abstract: In rats, acute exposure to hypoxia causes a decrease in mean arterial pressure (MAP) caused by a predominance of hypoxic vasodilation over chemoreflex-induced vasoconstriction. We previously demonstrated that exposure to chronic intermittent hypoxia (CIH) impairs hypoxic vasodilation in isolated resistance arteries; therefore, we hypothesized that the acute systemic hemodynamic responses to hypoxia would be altered by exposure to CIH. To test this hypothesis, rats were exposed to CIH for 14 days. Heart rate (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 54 publications
5
31
0
Order By: Relevance
“…These structural changes are consistent with our previous finding that CIH causes a leftward shift of the stress-strain relationship in gracilis arteries, indicating an increase in vessel stiffness (Phillips et al, 2006). The mechanisms underlying CIH-induced structural alterations are not known; however, we speculate that surges in arterial pressure and flow during intermittent hypoxia cycles, along with elevations in baseline blood pressure (Marcus et al, 2009a), initiate vascular remodeling aimed at normalizing wall stress. Previous investigators demonstrated, in cultured human endothelial cells, that one episode of hypoxia/reoxygenation was sufficient to enhance production of metalloproteinases responsible for degradation of vascular basement membrane and extracellular matrix, an important initial step in the remodeling process (Ben-Yosef et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These structural changes are consistent with our previous finding that CIH causes a leftward shift of the stress-strain relationship in gracilis arteries, indicating an increase in vessel stiffness (Phillips et al, 2006). The mechanisms underlying CIH-induced structural alterations are not known; however, we speculate that surges in arterial pressure and flow during intermittent hypoxia cycles, along with elevations in baseline blood pressure (Marcus et al, 2009a), initiate vascular remodeling aimed at normalizing wall stress. Previous investigators demonstrated, in cultured human endothelial cells, that one episode of hypoxia/reoxygenation was sufficient to enhance production of metalloproteinases responsible for degradation of vascular basement membrane and extracellular matrix, an important initial step in the remodeling process (Ben-Yosef et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Previously, we measured arterial pressure by telemetry in rats exposed to the identical CIH paradigm for 14 days (Marcus et al, 2009a). In that experiment, CIH increased mean arterial pressure during the portion of the day when the intermittent hypoxia cycles occurred and also during the portion of the day when the animals were unperturbed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, arterial blood pressure during hAIHT has been shown to normalize to baseline shortly after the IH exposure while MSNA remains elevated (Cutler et al , 2004). Animal studies utilizing IH exposures indicate that at least 1 day of IH is required to elicit sustained increases in MAP that persist beyond the IH exposure (Marcus et al , 2009; Mifflin et al , 2015), while human studies suggest that as little as 4–6 hours is required (Foster et al , 2010). Hence, we postulate that sustained arterial blood pressure elevations between hyperacute versus longer IH protocols are likely due to slow elevations in circulating neurohormones, such as endothelin and catecholamines (Kanagy et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It does not produce upper airway occlusions, negative intrathoracic pressure swings or sleep disruption, and it causes hypocapnia rather than hypercapnia. These features, along with intermittent hypoxia, may be important determinants of OSA-induced vascular dysfunction; nevertheless, our model does recapitulate the OSA phenotype in several ways (that is, endothelial dysfunction [31], blood pressure elevation [61,62], increased sympathetic nervous system activity [62] and increased vascular stiffness [63]). Our model is advantageous in that it allowed us to evaluate the effects of allopurinol on vessel function in the absence of confounding effects of comorbid conditions and other medications.…”
Section: Discussionmentioning
confidence: 99%